2019
DOI: 10.1029/2019jb017986
|View full text |Cite
|
Sign up to set email alerts
|

Plio‐Quaternary Outer Forearc Deformation and Mass Balance of the Southern Costa Rica Convergent Margin

Abstract: Identifying the processes that control the rates, magnitudes, and longevity of outer forearc deformation is fundamental to our understanding of how mass is distributed within subduction zone systems. The margin of southern Costa Rica has been the target of numerous onland field studies, geophysical surveys, and the Costa Rica Seismogenesis Project (CRISP) drilling expedition. Despite these extensive data sets, the relative roles that subduction erosion, shortening, and seamount subduction play in shaping the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 80 publications
(385 reference statements)
1
15
0
Order By: Relevance
“…Additionally, studies have credited the Cocos Ridge for the recent uplift of the CT by means of flat slab subduction (Fisher et al, 2004;Morell et al, 2016Morell et al, , 2019. These studies have shown that over the last 1-3 million years the CT have been uplifted ∼2-3 km; however, this is problematic when looking at seismological and gravitational models, (Dzierma et al, 2011;Lücke & Arroyo, 2015), which observe a clear steeply subducting slab well below.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have credited the Cocos Ridge for the recent uplift of the CT by means of flat slab subduction (Fisher et al, 2004;Morell et al, 2016Morell et al, , 2019. These studies have shown that over the last 1-3 million years the CT have been uplifted ∼2-3 km; however, this is problematic when looking at seismological and gravitational models, (Dzierma et al, 2011;Lücke & Arroyo, 2015), which observe a clear steeply subducting slab well below.…”
Section: Discussionmentioning
confidence: 99%
“…These authors relate the uplift of the forearc basin from deep water to nearshore conditions (~800 m) at early Pleistocene (~2.3 Ma) with the arrival of the Cocos Ridge at the trench, while they connect the onset of the Cocos Ridge subduction later in the early Pleistocene (from 2.2 to 1.9 Ma) with high erosional rates at the base of the overriding plate that triggered net subsidence of ~1,200 m. Finally, they interpret the second pulse of uplift (~1,000 m) from the middle‐late Pleistocene to Holocene (from 1.9 Ma to present day) that interrupted subsidence, as the direct effect of the subduction of the thickened Cocos Ridge crust. In contrast, Edwards, Kluesner, Silver, and Bangs () suggest that vertical motions of the outer forearc are a summation of plate to plate changes (e.g., the southeastward Panama Fracture Zone triple‐junction migration) and episodic events (e.g., subducting plate relief), rather than a result of a particular continuous process (i.e., this would not be linked to the Cocos Ridge impact with the trench nor its continued subduction) (Morell et al, ). Our seismic images extend further landward than the 3‐D volume and support large‐scale crystalline‐basement‐involved thick‐skinned tectonics, which leads to uplift of seafloor and tilting of the entire forearc basin, possibly a late pulse of uplift related to the Cocos Ridge rather than smaller subducting relief like seamounts or plateaus.…”
Section: Discussionmentioning
confidence: 99%
“…To the south, subduction of the aseismic Cocos Ridge, a ∼18 km thick and ∼200 kmwide basaltic ridge 82 that rises ∼2000 m high above the surrounding seafloor ( Fig. 2), is associated with the landward retreat of the Middle America Trench 83,84 . Ocean drilling indicates ~1 km of uplift of the forearc continental shelf within only ~0.3 My, starting at ∼2±0.2 Ma, which was followed by equally fast subsidence of ∼1.5 km (refs.…”
Section: And Supplementarymentioning
confidence: 99%
“…An alternative hypothesis states that the arrival of the Cocos Ridge at the trench would cause horizontal shortening and thickening of the forearc, without mass loss, and thus trench retreat. In this model, the subduction of a much smaller seamount is required to explain the initial, rapid vertical forearc movements 84,87 . However, contemporaneous thickening and subsidence of the outer forearc is required 84,87 , inconsistent with the isostatic uplift predicted following subduction of an ∼18 km thick basaltic ridge.…”
Section: And Supplementarymentioning
confidence: 99%